Characterization of Lgr5+ Progenitor Cell Transcriptomes after Neomycin Injury in the Neonatal Mouse Cochlea - Zhang, Shasha; Zhang, Yuan; Yu, Pengfei; Hu, Yao; Zhou, Han; Guo, Lingna; Xu, Xiaochen; Zhu, Xiaocheng; Waqas, Muhammad; Qi, Jieyu; Zhang, Xiaoli; Liu, Yan; et al. (Frontiers in Molecular Neuroscience, 2017)
Lgr5+ supporting cells (SCs) are enriched hair cell (HC) progenitors in the cochlea. Both in vitro and in vivo studies have shown that HC injury can spontaneously activate Lgr5+ progenitors to regenerate HCs in the neonatal mouse cochlea. Promoting HC regeneration requires the understanding of the mechanism of HC regeneration, and this requires knowledge of the key genes involved in HC injury-induced self-repair responses that promote the proliferation and differentiation of Lgr5+ progenitors. Here, as expected, we found that neomycin-treated Lgr5+ progenitors (NLPs) had significantly greater HC regeneration ability, and greater but not significant proliferation ability compared to untreated Lgr5+ progenitors (ULPs) in response to neomycin exposure. Next, we used RNA-seq analysis to determine the differences in the gene-expression profiles between the transcriptomes of NLPs and ULPs from the neonatal mouse cochlea. We first analyzed the genes that were enriched and differentially expressed in NLPs and ULPs and then analyzed the cell cycle genes, the transcription factors, and the signaling pathway genes that might regulate the proliferation and differentiation of Lgr5+ progenitors. We found 9 cell cycle genes, 88 transcription factors, 8 microRNAs and 16 cell-signaling pathway genes that were significantly upregulated or downregulated after neomycin injury in NLPs. Lastly, we constructed a protein-protein interaction network to show the interaction and connections of genes that are differentially expressed in NLPs and ULPs. This study has identified the genes that might regulate the proliferation and HC regeneration of Lgr5+ progenitors after neomycin injury, and investigations into the roles and mechanisms of these genes in the cochlea should be performed in the future to identify potential therapeutic targets for HC regeneration.